2000
DOI: 10.1023/a:1006308619659
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast cancer: clinical course, prognosis and therapy related to the first site of metastasis

Abstract: Although metastasis is a frequent event in breast cancer patients, insight into the clinical course, prognosis and therapy with respect to the site of the first metastases has been poor and contradictory in former investigations. Follow-up data from 648 patients with metastatic breast cancer were statistically analyzed. Patients with bone metastases at first relapse had better overall survival (median 71 vs. 48 months; p < 0.001) and survival after first metastases (median 24 vs 12 months; p < 0.001) than pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
189
1
18

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(222 citation statements)
references
References 25 publications
14
189
1
18
Order By: Relevance
“…A shorter metastasis-free interval also had a negative impact on survival in patients with bone metastases. This confirms previous work recognising the prognostic importance of the metastasis-free interval (Solomayer et al, 2000). A short metastasis-free interval also tends to suggest a more aggressive, rapidly growing tumour.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A shorter metastasis-free interval also had a negative impact on survival in patients with bone metastases. This confirms previous work recognising the prognostic importance of the metastasis-free interval (Solomayer et al, 2000). A short metastasis-free interval also tends to suggest a more aggressive, rapidly growing tumour.…”
Section: Discussionsupporting
confidence: 89%
“…Low-grade and ER-positive tumours were more likely to be associated with the development of bone metastases. Others have also found similar relationships (Koenders et al, 1991;Coleman et al, 1998;Solomayer et al, 2000). The same factors were also found to influence survival in patients presenting with bone metastases.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A recent study showed that compared with patients with visceral metastases with or without bone metastases, patients with bone‐only metastases at start of first‐line therapy had an improved median OS (54 months vs 28 months) 29. Other studies also found that the median survival of patients with bone‐only metastases was approximately twofold to threefold that of patients with additional visceral metastases 30, 41, 42, 43. The results of our cohort study reached the same conclusion that patients with metastases to the bone only had better survival than those with metastases to both the bone and extraosseous sites.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced breast cancer patients with visceral metastases (VM) are often regarded as having a worse prognosis and being less likely to respond to hormonal therapy than those with metastases in soft tissue and bone [1]. To date, cytotoxic therapies have provided the mainstay of treatment for patients with VM, with various mono-and polychemotherapy regimens proving efficacious in such patients [2,3].…”
Section: Introductionmentioning
confidence: 99%